An automated method for requirement determination and structuring based on 5W1H elements - A. Jabar, Marzanah; Ahmadi, Ramin; Shafazand, Mohammad Yaser; Abdul Ghani, Abdul Azim; Sidi, Fatimah; Hasan, Sa'adah (IEEE (IEEEXplore), 2013)
Information requirement determination is an important phase of software development. Since it happens at the beginning stages of software development, improvement in this process may lead to significant results for the entire software development. However, it is widely admitted that most of the conventional methods for collecting and analyzing requirements are not successful because several weaknesses such as lack of a certain automatic tool to elicit and analyze knowledge, or a well-structured model to facilitate the generation, analysis, and presentation of information requirements. In this paper, we discuss an integrated method to improve Information requirement determination and structuring in software development by asking questions based on 5W1H model of knowledge structure. Our unique contribution is that the proposed method uses a data mining method known as part-of-speech tagging tailored for requirement analysis to identify and organize target elements and their dependencies. We conduct experiments on a case study, demonstrating effectiveness of the method.